SPHK2 Knockdown Inhibits the Proliferation and Migration of Fibroblast-Like Synoviocytes Through the IL-17 Signaling Pathway in Osteoarthritis - Zheng J; Xiong X; Li K; Wang G; Cao H; Huang H (Dove Medical Press, 2024)
Jiaxuan Zheng,1,* Xiaolong Xiong,2,* Ke Li,2,* Guangji Wang,2 Huiyuan Cao,2 Hui Huang2 1Department of Pathology, Hainan General Hospital (Hainan Affiliated Hospital of Hainan Medical University), Haikou City, Hainan Province, 570311, People's Republic of China; 2Department of Sports Medicine, Hainan General Hospital (Hainan Affiliated Hospital of Hainan Medical University), Haikou City, Hainan Province, 570311, People's Republic of China*These authors contributed equally to this workCorrespondence: Hui Huang, Department of Sports Medicine, Hainan General Hospital (Hainan Affiliated Hospital of Hainan Medical University), No. 19 Xiuhua Road, Haikou City, Hainan Province, 570311, People's Republic of China, Tel +86-15108938272, Email 120653927@hainmc.edu.cnObjective: Synovial inflammation is vital for the progression of osteoarthritis (OA). The objective of this study was to explore the effects and potential molecular mechanisms of sphingosine kinase 2 (SPHK2) on the proliferation and migration of fibroblast-like synoviocytes (FLS).Methods: A TNF-α-stimulated FLS model and a papain-induced OA rat model were constructed. The functions of SPHK2 knockdown in OA were explored by a series of in vivo and in vitro assays. Downstream target genes of SPHK2 were investigated using transcriptome sequencing and validated by reverse transcription quantitative PCR (RT-qPCR). The effects of the SPHK2/IL-17 signaling pathway on inflammation, proliferation, and migration of OA-FLS were investigated using the IL-17 pathway inhibitor (secukinumab) and the activator (rhIL-17A).Results: TNF-α stimulation promoted SPHK2 expression at mRNA and protein levels in OA-FLS. SPHK2 knockdown reduced IL-1β, IL-6, MMP-2, MMP-9, cyclinD1, and PCNA levels and suppressed proliferation and migration of OA-FLS. SPHK2 knockdown alleviated cartilage damage and synovial inflammation in the OA rat model. LRRIQ3, H4C8, CXCL1, CABP4, COL23A1, and PROK2 expression levels were regulated by SPHK2. SPHK2 knockdown inhibited the protein levels of IL-17A, IL-17RA, and Act1. The IL-17 pathway inhibitor secukinumab enhanced the inhibitory effect of SPHK2 knockdown on the proliferation and migration of OA-FLS, while the IL-17 pathway activator rhIL-17A exerted the opposite effect.Conclusion: SPHK2 knockdown inhibits proliferation and migration of OA-FLS by blocking the IL-17 pathway, which provides a novel approach to the OA treatment.Keywords: sphingosine kinase 2, fibroblast-like synoviocyte, IL-17 signaling pathway, proliferation, migration